Development of Korean EFL Learners’ Learning Attitude using Flash-Based Animated Books - Tecnam Yoon (Journal of Education and Learning (EduLearn), 2016)
The purpose of this study is intended to identify the effectiveness of flash-based animated books when applied to the EFL elementary English class. As a teaching material, a flash-based animated book was chosen and discussed in order to figure out any changes of learners’ attitude toward English learning. Given the analysed data which were collected mainly through questionnaires and interviews with focal participants, findings suggested that flash-based animated books provided EFL students with rich content context, and created an interactive learning environment by promoting their motivation.